FORMATION OF NON-STANDARD THINKING IN THE LESSONS OF MATHEMATICS IN JUNIOR SCHOOLCHILDREN - Fozilov Jakhongir Ibrokhimovich; Topvoldiyeva Zuxraxon Ravshan qizi2; Abduraxmonova Mohinur Furqatjon qizi3 (American Journals, 2022)
The article is devoted to an important and significant topic for primary general education - the formation of non-standard thinking in mathematics lessons for younger students. Approaches to the formation of creative thinking of primary school students are analyzed, the main types of non-standard arithmetic problems are described, and solutions to these issues are given.
Keywords: non-standard tasks,; logical thinking,; extracurricular activities